Assessing Knowledge, Attitude and Practice of Materiovigilance among Pharmacy Students in South Kerala: A Cross-Sectional Study - Dharman, Dhanya; M L, Lal Prasanth; Mohan, Nitha P; Vijayan, Silpa (Indian Journal of Pharmacy Practice)
Aim: This cross-sectional study examined the knowledge, attitudes and practices regarding materiovigilance among pharmacy students in Kerala, conducted over 6 months from November 2022 to May 2023, with approval from the institutional ethics committee. Materials and Methods: A self-administered questionnaire was created based on previous research, divided into two sections: the 1st collected demographic data and the second contained 15 questions about materiovigilance. The questionnaire was distributed via Google Forms through WhatsApp and LinkedIn. Results: The study found that most respondents were aged 18-25, with females making up 67.11% of the sample. In total, 74.58% of respondents identified as female compared to 25.42% male, suggesting that findings may primarily reflect female perspectives. The results revealed that 89. 83% believed medical devices could lead to adverse events and 37% felt reporting this events was necessary. Additionally, 87.29% agreed that healthcare professionals should report such events and 96. 61% acknowledged that doing so enhances patient safety. However, only 21.19% had encountered adverse events and of those, 80.51% had not reported them. Alarmingly, 65.25% were unaware of any reporting forms, indicating a gap in necessary knowledge. Furthermore, 58.47% did not take patient feedback after implanting devices and 80. 51% had not attended workshops on medical devices. Conclusion: Most respondents recognized the risks associated with medical devices and the need for reporting. However, barriers such as lack of awareness, inadequate training and limited participation in reporting systems were evident. Many were not familiar with the classification system for medical devices. A significant portion (32.2%) lacked knowledge of existing monitoring programs. The gender disparity in responses may affect interpretations and suggests a need for balanced representation in future studies. In conclusion, while awareness of the importance of reporting adverse events exists among healthcare professionals, major gaps persist in education, engagement and system accessibility. Enhancements in training, awareness and patient feedback collection are crucial to improve materiovigilance practices and ensure patient safety in medical device usage.
Keywords: Adverse events; Materiovigilance; Medical Devices